The comparison of implementation and non-implementation Standard Operation Procedure (SOP) in practicing field activities for oil palm production / Filzah Hanis Abdul Kadir - Abdul Kadir, Filzah Hanis (Faculty of Plantation and Agrotechnology, 2018)
Princeton University and the Swiss Federal Institute of Technology had estimated between years 1990 until 2010, 55-60% of oil palm was expansion in Malaysia and Indonesia occurred at the expense of virgin forests. In addition, the oil palm industry also produce, the negative impact on the environment like open burning, higher chemical toxic in the soil and water pollution. So, the standard operation procedure (SOP) document a very helpful manager to easy control all the management, environment and activities of workers in plantation. Aim of this study which are to compare the implementation of SOP with non– implementation of SOP in field area, to investigate the most practices activities affect the yield of oil palm and to identify the relationship of field practice and yield of oil palm. The primary data have been collected on smallholders at Batu Anam, Segamat, Johor with involved four villages which are Kampung Sepang Loi, Kampung Mensudut Pindah, Kampung Awat and Kampung Pudu through distributed structure questionnaire. The data were analyzed by descriptive analysis, regression, correlation and t-test through SPSS version 24. This study show, that the most practices activities that effect oil palm yield is harvesting. Besides that, it found there are have significant different between the implementation SOP and non-implementation of SOP in term of yield. As conclusion, most of smallholders are not the implement SOP in handling the field activities.